Gender gaps of the unemployed: What drives diverging labor market outcomes? - Christine Martina Dauth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Analyzing gender gaps of unemployed job-seekers, this study uniquely complements the broad literature focussing predominantly on gender gaps of employed workers. I consider a broad range of labor market outcomes, and disentangle the factors driving the labor market gaps of unemployed men and women. I show that unemployed women perform worse on the labor market due to earlier choices in occupations, their labor force attachment, and working time. By contrast, regional labor market disparities including differences of local employment offices, which are assigned to place unemployed job-seekers, are of minor importance. Married women and those with young children perform particularly bad compared to men. High unexplainable gender gaps for these groups suggest that family-related preferences, employer discrimination, and institutional settings matter for unemployment duration and the quality of reemployment. – – Diese Studie untersucht Geschlechterunterschiede von arbeitslosen und arbeitssuchenden Personen. Sie ergänzt damit zahlreichen Studien, die sich mit der Geschlechterlohnlücke von Beschäftigten befassen. Ich untersuche den Arbeitsmarkterfolg anhand verschiedener Zielgrößen und identifiziere jeweils die Faktoren, die Geschlechterunterschiede von Arbeitslosen forcieren. Arbeitslose Frauen schneiden am Arbeitsmarkt vor allem wegen früherer Entscheidungen bezüglich ihrer Berufswahl, Teilzeitarbeit und ihrer Nähe zum Arbeitsmarkt schlechter ab. Regionale Disparitäten, unter anderem mögliche Vermittlungsunterschiede zwischen den lokalen Arbeitsagenturen, sind weniger wichtige Erklärungsfaktoren. Verheiratete Frauen und Frauen mit Kindern schneiden im Vergleich zu Männern besonders schlecht ab. Für diese Personengruppen gibt es relativ große nicht erklärbare Geschlechterunterschiede, was darauf hinweist, dass familienbezogene Präferenzen, Arbeitgeberdiskriminierung und institutionelle Rahmenbedingungen für sie besonders wichtig sind.
Keywords: J16; J21; J64; J71; 330; gender; labor market discrimination; decomposition; unemployment